Seroprevalence of melioidosis among livestock in Malaysia from 2000-2009 - H. I., Musa; Hassan, Latiffah; Rachmat, R. F. N.; Panchadcharam, Chandrawathani; Zakaria, Zunita; Abdul Aziz, Saleha (Department of Veterinary Services Malaysia, 2012)
Melioidosis usually results in chronic debilities that reduce the productivity of animals and condemnation of carcasses in abattoir. Melioidosis is reemerging among animals and humans, and anecdotal reports suggest an increase in disease observation. This study described the seroprevalence of melioidosis in livestock based on the data obtained from the Department of Veterinary Services, Putrajaya and the Veterinary Research Institute, Ipoh. The data were summarized according to animal species, state, and year. The seroprevalence rate in animals was 7.6, 48.2, 2.6, 13.6 and 3.6% in cattle, buffaloes, goats, sheep and pigs respectively. The seroprevalence of the disease varies in different states of the federation. For all species, the seroprevalence vary between 2.6% and 48.2%. The seroprevalence over the years increased from 4.2% in 2000 to 12.0% in 2003 after which it varies between the period 2004- 2007 and apparently declined between 2007 and 2009.